WEST-UKRAINIAN POLITICAL COMEDY OF THE 20-th-30-th YEARS OF THE XX CENTURY: MODIFIED GENRE - Rodchyn, Z. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The object of the article is a political comedy as well as its place in West-Ukrainian drama of the second-third decades of the last century. Symbolic attributes of the analyzed genre, poetics peculiarities of Western Ukrainian writers’ works are in the centre of the research.